"Welfare impact of electricity subsidy reforms in Pakistan: A micro model study". (February 2020) - Khalid, Syed Adnan; Salman, Verda
Abstract: Electricity subsidies in developing countries have always been debated in economics circles. Despite their popular appeal of providing relief to the poor, the research has proven otherwise. They increase the magnitude of deadweight loss and taper consumer welfare. However, complete withdrawal of a subsidy will make electricity unaffordable for the underprivileged. Therefore, in the context of developing countries, there is a need to determine the optimal level of subsidy, which will have the least economic impact and benefit the maximum number of users. Pakistan has been marred by deep energy crises and the government is forced to provide very large subsidies for electricity. Using Pakistan as a case study, this study uses a uniform and non-uniform price increase to determine the optimal level of electricity subsidies. This study employs a micro-model technique for the calculation of deadweight and welfare losses when the price of electricity is increased uniformly or non-uniformly across different consumption groups. This study also introduces a targeted subsidy approach for curbing the mounting deadweight loss due to immense electricity subsidies. Our research has identified that the targeted subsidy approach not only generates fiscal savings but also improves the welfare of the vulnerable in society. Highlights: An inefficient electricity pricing mechanism generates a deadweight loss. Targeted subsidies generate fiscal savings and also improve welfare. Consumer welfare and deadweight loss are more sensitive to changes in subsidy wedge. Subsidy wedge, not price, should be the focus while setting electricity tariffs.